Na+:H+ exchange inhibition induces intracellular acidosis and differentially impairs cell growth and viability of human and rat hepatocarcinoma cells - García Cañero, Rafael; Trilla, C.; Pérez de Diego, Javier; Díaz-Gil, Juan José; Cobo, J.M. (My University, 2024)
Amiloride and its more potent analog, hexamethylene amiloride (HMA), inhibits Na+:H+ exchange and decreases intracellular pH in a concentration-dependent way in two human hepatocarcinoma cell lines and in a rat hepatocarcinoma cell line that differs in its phenotypic characteristics, resembling the clinical situation encountered in human hepatocarcinomas. After 24 h of exposure, DNA synthesis and cell protein content of the cultures decreases according to the concentration of the drugs and in parallel to Na+ exchange inhibition and the drop in pH(i) promoted. RNA and protein syntheses are less sensitive to its action. The above effects induced by HMA are accompanied by an abrupt decrease in cell viability and lysosomal integrity at 24 h. These effects develop gradually with the exposure time as does the increase in free radical production. Decreased viability is totally or partially restored by N-acetylcysteine or deferoxamine, but the degree of intracellular acidification produced is not. These results tend to suggest that intracellular acidification can diminish cell growth and provoke cytotoxic cell death by diminishing reduced glutathione (GSH) levels and impairing lysosomal integrity, reflecting the sensitivity of hepatocarcinoma cells to Na+ exchange inhibition and intracellular acidosis. Copyright (C) 1999 Elsevier Science Ireland Ltd.